2022
DOI: 10.2174/1568026622666220718155616
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase (IDO)-activity in Severe Psychiatric Disorders: A Systemic Review

Abstract: Background: Indoleamine 2,3-dioxygenase (IDO) activity is induced by cellular immune activation and therefore associated to inflammatory diseases, among others psychiatric disorders. This review aims to elucidate IDO activity reflected by kynurenine (KYN) to tryptophan (TRP) ratio in severe mental disorders. Methods: A systematic literature search in MEDLINE and EMBASE was conducted targeting clinical trials in English language measuring KYN/TRP in individuals with a diagnosis of depression, bipolar disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…The gene expression of indoleamine 2,3-dioxygenase (IDO) is determined by p38 MAPK, and the activity is induced by cellular immune activation associated with inflammatory diseases [68]. LPS induces the expression of IDO, and FA can pass through the blood-brain barrier to reduce IDO by suppressing the phosphorylation of p38 MAPK, which may provide new ideas for the prevention and treatment of diseases [69].…”
Section: P38 Mapkmentioning
confidence: 99%
“…The gene expression of indoleamine 2,3-dioxygenase (IDO) is determined by p38 MAPK, and the activity is induced by cellular immune activation associated with inflammatory diseases [68]. LPS induces the expression of IDO, and FA can pass through the blood-brain barrier to reduce IDO by suppressing the phosphorylation of p38 MAPK, which may provide new ideas for the prevention and treatment of diseases [69].…”
Section: P38 Mapkmentioning
confidence: 99%
“…In cardiac disease management, Rg3 chiefly functions by reducing inflammation and curtailing oxidative stress. Anti-inflammatory action is linked to the regulation of TRP/KYN metabolism, enhancing 5-HT and BDNF levels, and thereby alleviating mental disorders ( Kuo et al, 2021 ; Fellendorf et al, 2022 ; Gong et al, 2023 ). MDD is characterized by reduced antioxidant concentrations in plasma ( Bhatt et al, 2020 ).…”
Section: Rg3 In the Coexistence Of Cardiac Diseases And Psychiatric D...mentioning
confidence: 99%
“…Recent studies have reported that IDO activity, as reflected by Kyn/Trp ratio, shows significant differences in different types of mental disorders. However, the results of studies on Kyn/Trp calculations for severe mental disorders are inconsistent [82]. Therefore, with the important involvement of IDO in various vital metabolic activities, it is necessary to summarize the currently available methods for the determination of IDO activity, hoping to find a suitable method for the determination of IDO activity to be applied in clinical diagnosis and treatment.…”
Section: Applications Of Ido Activity Assaysmentioning
confidence: 99%